2022
DOI: 10.1097/01.hs9.0000843484.72409.00
|View full text |Cite
|
Sign up to set email alerts
|

S148: Venetoclax-Obinutuzumab for Previously Untreated Chronic Lymphocytic Leukemia: 5-Year Results of the Randomized Cll14 Study

Abstract: Background: Background:One-year fixed-duration venetoclax-obinutuzumab (Ven-Obi) has demonstrated significant improvement of progression-free survival (PFS) as compared to chlorambucil-obinutuzumab (Clb-Obi) in patients with previously untreated chronic lymphocytic leukemia (CLL) and coexisting conditions in the CLL14 trial. As high rates of undetectable minimal residual disease (uMRD) suggested deep remissions, long-term efficacy data including patients with high-risk disease is of particular interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The venetoclax-obinutuzumab arm showed longer PFS at 24 months (88.2 vs. 64.1%) and complete remission rate (49.5 vs. 23.1%) [112 ▪ ]. After 4 years of follow-up, there have been no differences in OS [113]. The main reported toxicities associated with venetoclax are not only grade 3–4 neutropenia, which is the most common adverse event, but also grade 3–4 thrombocytopenia and anaemia can occur.…”
Section: Pathway Inhibitorsmentioning
confidence: 90%
See 1 more Smart Citation
“…The venetoclax-obinutuzumab arm showed longer PFS at 24 months (88.2 vs. 64.1%) and complete remission rate (49.5 vs. 23.1%) [112 ▪ ]. After 4 years of follow-up, there have been no differences in OS [113]. The main reported toxicities associated with venetoclax are not only grade 3–4 neutropenia, which is the most common adverse event, but also grade 3–4 thrombocytopenia and anaemia can occur.…”
Section: Pathway Inhibitorsmentioning
confidence: 90%
“…Importantly, updates of the CLL14 trial and the Murano trial have reported that the presence of TP53 aberrations remain a poor response predictive factor for these regimens. In addition, in the front-line setting, patients with uIGHV had shorter duration of the response, the median PFS being 57.3 months vs. not reached in patients with mutated IGHV under venetoclax-obinutuzumab [113].…”
Section: Pathway Inhibitorsmentioning
confidence: 96%
“…Updated follow-up data were presented at the European Congress; and, at a median follow-up of 65.4 months, PFS was superior for venetoclaxobinutuzumab (not reached vs. 36.4 months; HR, 0.35). 19,20 The estimated 5-year PFS was 62.6% with this combination versus 27% in the chlorambucil arm. Notably, the PFS was substantially lower in patients with TP53 aberrations, who demonstrated a PFS of 52% at 4 years and 40.6% at 5 years.…”
Section: Frontline Venetoclax Therapymentioning
confidence: 99%
“…The estimated 5‐year PFS was 62.6% with this combination versus 27% in the chlorambucil arm. Notably, the PFS was substantially lower in patients with TP53 aberrations, who demonstrated a PFS of 52% at 4 years and 40.6% at 5 years 20,21 . As discussed below, this prompted cross‐trial comparisons with BTK inhibition, suggesting that—all other things being equal—fixed‐duration venetoclax‐obinutuzumab therapy may not be the ideal initial treatment regimen of choice in patients with this high‐risk aberration.…”
Section: Frontline Venetoclax Therapymentioning
confidence: 99%
“…2 At 5-year follow-up, VenO treated patients had improved PFS over ChlO; 62.6% vs. 27.0%. 7 In fit patients in GAIA/CLL13, VenO demonstrated superior PB uMRD rates (86.5% vs. 52.0%; p<0.0001) and PFS (HR 0.42 [97.5% CI 0.26-0.68); p<0.0001) compared with CIT (age-stratified fludarabine-cyclophosphamide-rituximab…”
mentioning
confidence: 98%